Contribution of Cervical Proprioception, Vision, and Vestibular Feedback on Reducing Dynamic Head–Trunk Orientation Error in the Yaw Direction - Mooti, Rami; Park, Hangue (Frontiers in Neuroscience, 2022)
The contribution of cervical proprioception, vision, and vestibular feedback to the dynamic head-trunk orientation error in the yaw direction was investigated to further the understanding over the mechanism of coordination among different sensory modalities for dynamic head-trunk orientation. To test the contribution of each sensory modality, individually and together, to dynamic head-trunk orientation, ten healthy human subjects participated in the extended cervical joint position error test, measuring the ability of repositioning the head back to the reference orientation after 45-degree yaw rotation of head or trunk. The error between initial and returned angles was measured. The test was repeated under eight different conditions of sensory feedback, with or without each of three sensory modalities. Each subject completed 64 trials (eight per condition) in a random order for fair comparison. No change was found in bias when one of the three modalities was missing, while variance was largest at the lack of dynamic cervical proprioception. When two of the three modalities were missing (i.e., one of the three modalities was present), both bias and variance were minimum at the presence of cervical proprioception. Additionally, both visual and vestibular feedback was redundant (i.e., no further improvement in both bias and variance), if the other one (visual or vestibular feedback) was present with dynamic cervical proprioception. In sum, the experimental results suggest that dynamic cervical proprioception is the most significant sensory modality for reducing the dynamic head-trunk orientation error in the yaw direction.